Characterization and transgenic study of CONSTANS-LIKE8 (COL8) gene in Arabidopsis thaliana: expression of 35S:COL8 delays flowering under long-day conditions - Nishiyama, Yuuki; Nakasone, Akari; Yasuhara, Masahiro; Takase, Tomoyuki; Tokioka-Ono, Yoko; Kiyosue, Tomohiro; Kakikubo, Yoshihiro (Plant Biotechnology, 2011)
CONSTANS (CO) is a regulator of photoperiodic flowering that activates the transcription of a florigen gene, FLOWERING LOCUS T (FT), in Arabidopsis. CO belongs to the CO/CONSTANS-LIKE (COL) protein family, which consists of 17 proteins and is subclassified into three groups. Here, we characterized the gene for one of the group II members, COL8. The COL8 mRNA accumulated in seeds, leaves, flowers, and siliques. Transgenic Arabidopsis plants with a beta-glucuronidase (GUS) reporter gene driven by a 3-kb COL8 promoter displayed strong GUS activity in leaves. Both transiently and stably produced fluorescence-tagged COL8 proteins were localized in the nucleus. Transgenic Arabidopsis plants possessing COL8 cDNA driven by a cauliflower mosaic virus (CaMV) 35S promoter did not show any altered circadian rhythm under constant light conditions, but showed a late-flowering phenotype under long-day conditions. In these transgenic plants, CO mRNA did not decrease from zeitgeber time (zt) 12 to zt 16, whereas FT mRNA decreased from zt 8 to zt 24. The possible mechanisms for the late-flowering phenotype of the COL8 plants driven by the CaMV 35S promoter are discussed.